The Influence of the Change of the 2013 Curriculum to the Merdeka Curriculum on the Achievement of the School’s Vision and Mission in Madrasah Ibtidaiyyah - Zanella amelia Ananda; Amaliyah Ananda Baharudin; Ulfa Hasana (At-Taqaddum, 2023)
Along with the development of the times, of course, there are more and more demands to improve quality in the field of education. Therefore, the Ministry of Education and Culture launched a new curriculum policy called the Merdeka Belajar to initiate this matter. This policy addresses four topics: the flexibility of educators in compiling teaching modules, providing leeway in regulating the acceptance of new students, and several other new policies in terms of instilling the character of Pancasila for students. Thus, changing from the 2013 curriculum to the Merdeka Curriculum triggers new challenges that can significantly impact learning outcomes. These challenges can plunder educators in terms of aspects of the media used, different and far more comprehensive assessment systematics, the methods used to convey the learning material they want to teach, and schools in achieving their vision and mission.